Analysis of Lake Water Quality in Cimahi City, West Java Province - Eka Wardhani; Nurul Aulia Fitriani; Virgy Vania Gary Apsari; Faza Kamilah Kusnadi; Fitra Insyirah Rachmanita (Universitas Diponegoro, 2023)
Cimahi City is experiencing raw water insecurity. This requires the local government to look for new water sources, such as rehabilitating the condition of existing lakes in their area so that they function again as raw water lake. This study aims to analyze water quality and parameters that exceed quality standards and to calculate the status of lake water quality. The data will be the basis for preparing priority recommendations for lake management. The calculation of this method uses the Pollution Index (PI) method. The lakes studied were lakes located at the Cimahi City Government location, at the Cibabat Hospital, Setiamanah, Ciseupan, and the Cimahi City Infantry Brigade Complex. Based on research results in 2021, all lakes will be in the moderately polluted category, while in 2022 they will be in the low-moderate pollutant category. Lake water quality that has improved is Setiamanah Lake and that in the Cimahi City Infantry Brigade Complex. The two lakes originally had moderate to moderate polluted status with an index value of 8.40 to 4.94, so efforts and control strategies are needed to reduce pollution in the 5 lakes.